Dreamweaver CC essentials (John Wiley & Sons, 2013)
"Master Dreamweaver CC on your own terms with this one-of-a-kind video training course Dreamweaver is Adobe's robust web design and development software used by creative professionals to design websites and mobile applications, and Dreamweaver CC is packed with the tools you need to create dynamic and interactive sites online. Now, you can learn the ins and outs of maximizing Dreamweaver CC - from navigating the interface to working with HTML, CSS, jQuery, and more - with Dreamweaver CC Essentials. Our instructors provide expert, straight-forward, user-friendly training to help you tackle new topics the way you want to learn. Master basic skills, boost your creativity, and challenge yourself in bold new directions. Get to know HTML and how it can be used to set up your own customized website Add text and images, create page layouts, work with web fonts and tables, and fine tune your workflow for maximum efficiency Gain expert knowledge on site design, including designing for mobile devices and utilizing the jQuery UI library Incorporate multimedia like video, audio, interactive content, HTML forms, and other tools into your web development projects Includes over 12 hours of Dreamweaver CC video training."--Resource description page.